Nostalgic Frontiers: Violence Across the Midwest in Popular Film - (:unkn) unknown (My University, 2014)
In "Nostalgic Frontiers: Violence Across the Midwest in Popular Film," I analyze the temporality and politics of nostalgia while providing a critical history of Midwestern representations in popular culture from the turn of the twentieth century through the first decade of the new millennium. A general line of inquiry informs this project: how do narratives set in the Midwest imagine, reify, and reproduce Midwestern identity, and what are the repercussions of such regional imagery circulating in American culture? Throughout this project, I identify shifting cultural perceptions of the Midwest at particular historical moments. In relation to these regional considerations, I analyze two modes of nostalgia: as a spatial element that is mapped onto the Midwest's landscape and as a cultural force that regulates Midwesterners with violence. I developed the concept of "nostalgic violence" in order to theorize violent attempts to reshape the present in relation to idealized images of the past in Midwestern narratives. Overall, with "Nostalgic Frontiers," I work to more fully integrate nostalgia and regional study into the diverse field of media studies by assessing how ideological and historical factors are filtered through cinema, thus shaping our understanding of the Midwest.
Keywords: Film; Literature; Midwest; Nostalgia; Violence